The immune microenvironment in EGFR- and ERBB2-mutated lung adenocarcinoma - Kirchner, Martina; Kluck, Klaus; Brandt, Regine; Volckmar, Anna-Lena; Penzel, Roland; Kazdal, Daniel; Endris, Volker; Neumann, Olaf; Şeker-Cin, Huriye; Goldschmid, Hannah; Glade, Julia; Allgäuer, Michael; et al. (ESMO open, 2021)
Background - Targeted therapies have improved survival and quality of life for patients with non-small-cell lung cancer with actionable driver mutations. However, epidermal growth factor receptor (EGFR) and human epidermal growth factor receptor 2 gene (HER2, also known as ERBB2) exon 20 insertions (Ex20mut) are characterized by a poor response to currently approved tyrosine kinase inhibitors and immunotherapies. The underlying immune biology is not well understood. - Materials and methods - We carried out messenger RNA expression profiling of lung adenocarcinomas (ADCs) with ERBB2 (n = 19) and EGFR exon 20-insertion mutations (n = 13) and compared these to tumors with classical EGFR mutations (n = 40, affecting EGFR exons 18, 19 or 21) and EGFR/ERBB2 mutation-negative lung ADC (EGFR/ERBB2wt, n = 26) focusing on immunologically relevant transcripts. Tumor-infiltrating immune cells were estimated from gene expression profiles. - Results - Cytotoxic cells were significantly lower in EGFR-mutated tumors regardless of the affected exon, while Th1 cells were significantly lower in EGFR-Ex20mut compared to EGFR/ERBB2wt tumors. We assessed the differentially expressed genes of ERBB2-Ex20mut and EGFR-Ex20mut tumors compared to EGFR-Ex18/19/21mut and EGFR/ERBB2wt tumors. Of these, the genes GUSB, HDAC11, IFNGR2, PUM1, RASGRF1 and RBL2 were up-regulated, while a lower expression of CBLC, GBP1, GBP2, GBP4 and MYC was observed in all three comparison groups. The omnibus test revealed 185 significantly (FDR = 5%) differentially expressed genes and we found these four most significant gene expression changes in the study cohort: VHL and JAK1 were overexpressed in ERBB2-Ex20mut and EGFR-Ex20mut tumors compared to both EGFR-Ex18/19/21mut and EGFR/ERBB2wt tumors. RIPK1 and STK11IP showed the highest expression in ERBB2-Ex20mut tumors. - Conclusions - Targeted gene expression profiling is a promising tool to read out the characteristics of the tumor microenvironment from routine diagnostic lung cancer biopsies. Significant immune reactivity and specific immunosuppressive characteristics in ERBB2-Ex20mut and EGFR-Ex20mut lung ADC with at least some degree of immune infiltration support further clinical evaluation of immune-modulators as partners of immune checkpoint inhibitors in such tumors.